Oman's policy within the Gulf Cooperation Council Towards the Iraq-Iran war - Abed Reden, Ass.Lecture Hassan Ghanim (Thi Qar Arts Journal, 2022)
Oman is characterized by an important geographical location, which made it a country of great commercial importance and an influential factor in the level of foreign policy and the challenges that cast a shadow over the security and stability of the Arab Gulf region in general, in light of the narrow political alignments and axes witnessed by the international and regional political arena, which represent a real challenge to the security and strategy The countries of the Arab Gulf region, The Sultanate of Oman has followed a clear approach and firm ways to proceed according to specific rules regarding joint Gulf action towards the most serious challenges facing the Arab Gulf region at the regional and international levels, by following the language of dialogue and standing on impartiality and non-alignment with any of the regional or Arab parties in order to Maintaining security and stability in the region in general.